The evolution of Cow's Milk-related Symptom Score (CoMiSS™) in presumed healthy infants - Bajerova, Katerina; Hrabcova, Karolina; Vandenplas, Yvan (European journal of pediatrics, 2024)
The Cow's Milk-related Symptom Score (CoMiSS™) is a scoring system that reflects the appearance and intensity of symptoms possibly related to consumption of cow's milk. The original tool was recently updated by changing the cut-off, and the stool scale and by adding angioedema. There is no data available regarding the natural evolution of CoMiSS in infants with no cow's milk allergy (no-CMA) or a comparison between original and updated CoMiSS values. We determined the original and the updated CoMiSS in infants not diagnosed with cow's milk allergy. The evolution of CoMiSS during the first year of life was assessed repetitively during predefined check-ups at 1.5, 3, 4, 6, 8, 10, and 12 months. The original and updated scores were compared with the Wilcoxon Signed-Rank Test. We also tested the impact of feeding type, age, gender, and order in the family on the CoMiSS. One hundred and twenty-two infants were included. CoMiSS values during the first year of life showed an inverse relation to age. The difference in CoMiSS between the original and updated versions was significant at 6,8,10, and 12 months (p < 0.001), related to the switch from the Bristol Stool Form Scale to the Brussels Infants and Toddlers Stool Scale (BITSS). The difference between both versions of CoMiSS was not significantly different in infants < 6 months (p = 0.999 at 1.5 and 4 months, and p = 0.586 at 3 months, respectively).Conclusion: CoMiSS decreases with age during the first year of life. While there is no difference between the two CoMiSS versions in healthy infants under 6 months of age, the CoMiSS value in the updated version is lower than the original 1 in infants aged 6 to 12 months. What is known? • The Cow's Milk-related Symptom Score (CoMiSS) is a validated awareness tool for cow's milk allergy (CMA). • A CoMiSS of ≥ 10 indicates a risk for cow's milk allergy. What is new? • The natural evolution of CoMiSS in infants not diagnosed with CMA (no-CMA) shows an inverse relation to age. • There is no difference between the original and the updated CoMiSS versions in no-CMA-infants under six months of age, but the updated CoMiSS is lower in infants 6-12 months than the original one.
Keywords: Animals; Female; Infant; novorozenec; ženské pohlaví; lidé; Infant, Newborn; Milk; stupeň závažnosti nemoci; Cow’s milk allergy; Male; kojenec; Milk Hypersensitivity; Awareness tool; mužské pohlaví; zvířata; mléko; Severity of Illness Index; alergie na mléko; CoMiSS; Humans